Abnormal Origin of the Right Pulmonary Artery From Ascending Aorta (Hemitruncus Arteriosus) - L. Julian Haywood MD; Yervand Chakryan MD; Diana Kim MD; Tin Boltzer MD; Gregory Rivas MD; David Shavelle MD (SAGE Publishing, 2014)
Hemitruncus arteriosus is a rare congenital deformity that results in early infant mortality. Persistence into adulthood is very unusual and is associated with pulmonary hypertension. We report a case in an adult male with the associated clinical issues.